2020
DOI: 10.1002/brb3.1767
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix proteins are time‐dependent and regional‐specific markers in experimental diffuse brain injury

Abstract: The central nervous system (CNS) is composed of interacting compartments, including neurons, glia, vasculature, and cerebral spinal fluid. The extracellular matrix (ECM) links these compartments together through ligand-receptor interactions including integrins, cell adhesion molecules, and cell-surface glycoproteins. The ECM constitutes approximately 20% of the mature brain volume and is comprised of an intricate interconnected matrix of a variety of glycoproteins, proteoglycans, and glycosaminoglycans that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
2
17
0
4
Order By: Relevance
“…To analyze the mechanism by which 2ccPA contributes to the suppression of apoptosis via astrocytes, we focused on the extracellular matrix proteins. Recently, the protein levels of several extracellular matrix proteins, fibronectin, TN-C, and reelin has been reported to be changed in the acute phase of rat brains using experimental diffuse TBI model (Griffiths et al, 2020) and the modulation of extracellular matrix is a potential target of TBI treatment (George and Geller, 2018). Reactive astrocytes are known to express TN-C at extremely high levels when the brain is damaged (Laywell et al, 1992;, and there are many reports of TN-C expression in astrocytes around the injury site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the mechanism by which 2ccPA contributes to the suppression of apoptosis via astrocytes, we focused on the extracellular matrix proteins. Recently, the protein levels of several extracellular matrix proteins, fibronectin, TN-C, and reelin has been reported to be changed in the acute phase of rat brains using experimental diffuse TBI model (Griffiths et al, 2020) and the modulation of extracellular matrix is a potential target of TBI treatment (George and Geller, 2018). Reactive astrocytes are known to express TN-C at extremely high levels when the brain is damaged (Laywell et al, 1992;, and there are many reports of TN-C expression in astrocytes around the injury site.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by reports that acute changes in the levels of TN-C may indicate a restorative or regenerative response associated with recovery from TBI. (Griffiths et al, 2020), and that TN-C promotes locomotor recovery after spinal cord injury (Chen et al, 2010). TN-C deposition promotes fibrin accumulation in fibrosis, asthma, and cancer (Brellier et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant increase in fibronectin levels was observed within the hippocampus at three days post injury. The authors suggested that the acute changes in the levels of fibronectin are associated with circuit dismantling, while increases at post-acute time points indicate a potential restorative or regenerative response associated with recovery from TBI [ 35 ]. This observation in combination with the cytokine and A2A receptor signaling described above suggest that MA mediates neuroprotection by eliciting broad pleotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma fibronectin-deficient animals perform significantly worse on both motor and cognitive tasks, have significantly increased lesion volume, apoptotic cell death, and had significantly less phagocytic cells in the injured cortex compared to injured mice with normal pFn levels [34]. Recently, Griffiths et al (2020) reported a significant decrease in fibrinogen levels within the somatosensory barrel fields during the acute phase (15 min-2 h) post TBI [35]. However, a significant increase in fibronectin levels was observed within the hippocampus at three days post injury.…”
Section: Alterations In Specific Protein Clustersmentioning
confidence: 99%
“…In addition, an association with neurodegeneration in the underlying neural tissue had not been examined. By creating a focal cortical model, with inflammation extending down into the full depth of the sagittal sulcus as well as across the cortical surface, we have reproduced a number of features of the situation seen in MS, notably the presence of TLS neogenesis in deep sulci (Griffiths et al, 2020; Howell et al, 2011). It is likely that the reduced CSF flow in the deep sulcus would allow a local increase in cytokine concentration that might not be reflected by global concentrations, although no experimental data is available on such CSF flow rates in the rat.…”
Section: Discussionmentioning
confidence: 99%